Adjective Adverb Interfaces in Romance - Salvador Valera (Linguistik Aktuell/Linguistics Today, 2017)
Within the current discussion on grammatical interfaces, the word-classes of adjective and adverb are of particular interest because they appear to be separated or joined in manifold ways at the level of word-class or syntax, with morphology playing a prominent role, especially in Romance. The volume provides typological and theoretical insights into the common or different usage of adjectives and adverbs in Romance. Diachronic change is discussed alongside with synchronic variation and the representation in grammar. The discussion turns out to be controversial, calling into question traditional assumptions such as the dogma of the invariability and the categorial status of the adverb.